Rum, cover letters, networking, & interviewing - Eischen, Clifford W.; Eischen, Lynn A. (Mason, OH : South-Western, Cengage Learning, 2013)
Looks at how to use current business technologies to create a winning rumand includes coverage of the interview process, cover letters, networking, and job applications.
Rev. ed. of: Resumes, cover letters, networking, and interviewing. 3rd ed.
Includes bibliographical references.
Keywords: Resumes (Employment); Cover letters; Business networks; Interviewing